Gastrointestinal stromal tumor with small cell carcinoma infiltration: a case report - Zhou, Yitong; Song, Liyuan; Lyu, Li; Li, Shengjie; Wang, Qimin (Frontiers in Oncology, 2024)
Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the digestive system. They usually occur in the gastrointestinal tract. However, we discovered a rare phenomenon in which small cell carcinoma infiltrated a patient's GIST. The patient came to the hospital and presented with chest tightness and shortness of breath for two months and a dry cough for half a month. As the ancillary tests were refined, we discovered that he also had a lesion in the pelvic cavity. After pathological examination of core-needle biopsy (CNB) samples from the pelvic cavity lesion, we diagnosed the patient with GIST with small cell carcinoma infiltration. The patient is currently receiving chemotherapy with etoposide in combination with a cisplatin regimen.